2018
DOI: 10.4103/ijpvm.ijpvm_263_17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coenzyme Q10 supplementation on serum of high sensitivity c-reactive protein level in patients with cardiovascular diseases: A systematic review and meta-analysis of randomized controlled trials

Abstract: Possible effects of coenzyme Q10 (CoQ10) supplement on the serum level of high-sensitivity C-reactive protein (hs-CRP) in cardiovascular diseases (CVDs) remains unclear.Objective:Therefore, this meta-analysis was conducted to investigate its effects on the serum hs-CRP level in patients with CVDs. A comprehensive search was conducted on the EMBASE, MEDLINE, and PubMed Central databases for pertinent papers in English up to November 2016. All randomized controlled trials (RCTs) that studied the effects of suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…48 A meta-analysis suggested that supplementation with CoQ10 significantly reduced circulating hsCRP in patients whose baseline levels of hsCRP were more than 3 mg L −1 . 51 Combining this meta-analysis with our results, it is suggested that there may be a more significant negative association between dietary CoQ10 and circulating hsCRP in subgroups with higher levels of hsCRP. These speculations need to be further confirmed by cohort studies.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…48 A meta-analysis suggested that supplementation with CoQ10 significantly reduced circulating hsCRP in patients whose baseline levels of hsCRP were more than 3 mg L −1 . 51 Combining this meta-analysis with our results, it is suggested that there may be a more significant negative association between dietary CoQ10 and circulating hsCRP in subgroups with higher levels of hsCRP. These speculations need to be further confirmed by cohort studies.…”
Section: Discussionsupporting
confidence: 68%
“…According to the recent meta-analyses of RCTs, 22,50–53 CoQ10 supplementation may reduce the risk of inflammation-related diseases by partly reducing the levels of several circulating inflammatory markers, including CRP, IL-6, and TNF-α. Zahed et al found that three months of 100 mg per day CoQ10 intervention significantly reduced CRP and thus cardiovascular events in a randomized cross-over clinical trial of 34 patients with end-stage renal disease undergoing dialysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no changes were observed for CRP or IL-6. Finally, in patients with CVD with baseline serum hs-CRP levels > 3 mg/L, these levels improved after receiving CoQ10 supplementation for more than 12 weeks (146).…”
Section: Coenzyme Q10mentioning
confidence: 99%